Changes in yield and grain quality characteristics of irrigated rice (Oryza sativa) genotypes under aerobic conditions - Singh, Naveen; Kaur, Rupinder; Sharma, Neerja; Mahajan, Gulshan; Bharaj, T S (The Indian Journal of Agricultural Sciences, 2012)
Twenty-seven rice (Oryza sativa L.) genotypes were evaluated in two planting systems, viz. aerobic (dry direct seeded) and conventional flood irrigated transplanting under puddle conditions. There was a significant change in yield and morpho-physicochemical grain quality traits when grown under aerobic system of planting. Per cent yield reduction was varying between 2.45% in IR 71703-587-1-3 and 79.44% in IR 73435-8-2-2-1. Differences for days to 50% flowering, plant height and effective tillers/m2 were also observed over the planting systems. Planting systems significantly affected total rice recovery, head rice recovery, test weight of paddy, brown rice and milled rice, alkali spreading value and amylose content. However, grain length, grain breadth and L:B ratio were not affected. Genotypic differences over planting method for susceptibility index (SI) and mean relative performance were also observed. Genotypes which are suitable in flooded system may not be suitable for aerobic system. However, among these genotypes IR 73944-143-3-2-3-3, IR 71701-28-1- 4, PAU 201, IR 71703-587-1-3 and IR 72158-11-5-3-2 were found to be better candidates for the aerobic system. Possibility of improving rice yield and quality using genotypes suitable for aerobic system in the breeding programmes was explored.